Association Between Quantitative Diffusion-Weighted Magnetic Resonance Neuroimaging and Outcome After Pediatric Cardiac Arrest. (6th December 2022) - Kirschen, Matthew P.; Berman, Jeffrey I.; Liu, Hongyan; Ouyang, Minhui; Mondal, Antara; Griffis, Heather; Levow, Cindee; Winters, Madeline; Lang, Shih-Shan; Huh, Jimmy; Huang, Hao; Berg, Robert A.; et al.
Abstract : Background and Objectives: Diffusion MRI can quantify the extent of hypoxic-ischemic brain injury after cardiac arrest. Our objective was to determine the association between the adult-derived threshold of apparent diffusion coefficient (ADC) <650 × 10 −6 mm 2 /s in >10% of brain tissue and an unfavorable outcome after pediatric cardiac arrest. Since ADC decreases exponentially as a function of increasing age, we determined the association between (1) having >10% of brain tissue below a novel age-dependent ADC threshold, and (2) age-normalized whole-brain mean ADC and unfavorable outcome. Methods: This was a retrospective study of patients aged ≤18 years who had cardiac arrest and a clinically obtained brain MRI within 7 days. The primary outcome was unfavorable neurologic status at hospital discharge based on the Pediatric Cerebral Performance Category score. ADC images were extracted from 3-direction diffusion imaging. We determined whether each patient had >10% of voxels with an ADC below prespecified thresholds. We computed the whole-brain mean ADC for each patient. Results: One hundred thirty-four patients were analyzed. Patients with ADC <650 × 10 −6 mm 2 /s in >10% of voxels had 15 times higher odds (95% CI 5–65) of an unfavorable outcome compared with patients with ADC <650 × 10 −6 mm 2 /s (area under the receiver operating characteristic curve [AUROC] 0.72 [95% CI 0.63–0.80]). These ADC criteria had a sensitivity and specificity of 0.49 and 0.94, respectively, and positive and negative predictive values of 0.93 and 0.52, respectively, for an unfavorable outcome. The age-dependent ADC threshold that yielded optimal sensitivity and specificity for unfavorable outcomes was <300 × 10 −6 mm 2 /s below each patient's predicted whole-brain mean ADC. The sensitivity, specificity, and positive and negative predictive values for this ADC threshold were 0.53, 0.96, 0.96, and 0.54, respectively (odds ratio [OR] 26.4 [95% CI 7.5–168.3]; AUROC 0.74 [95% CI 0.66–0.83]). Lower age-normalized whole-brain mean ADC was also associated with an unfavorable outcome (OR 0.42 [0.24–0.64], AUROC 0.76 [95% CI 0.66–0.82]). Discussion: Quantitative diffusion thresholds on MRI within 7 days after cardiac arrest were associated with an unfavorable outcome in children. The age-independent ADC threshold was highly specific for predicting an unfavorable outcome. However, the specificity and sensitivity increased when using age-dependent ADC thresholds. Age-dependent ADC thresholds may improve prognostic accuracy and require further investigation in larger cohorts. Classification of Evidence: This study provides Class III evidence that quantitative diffusion-weighted imaging within 7 days postarrest can predict an unfavorable clinical outcome in children.